Marketing and Assessment in Academic Libraries: A Marriage of Convenience or True Love? - Porat, Lynne (Evidence Based Library and Information Practice, 2013)
Objective – This paper describes the process of cooperation between the Marketing and Assessment Teams at the University of Haifa in Israel, from initial apprehension about working together to the successful marketing of a suite of user studies. Methods – The first step was a formal meeting in which the leader of the assessment team explained the aims of assessment. For each assessment activity, the assessment team submitted a formal request for assistance to the marketing team, conducted team meetings on how to market each assessment, and met with the marketing team to explain the survey and receive their input on how it should be marketed. Over a 3-year period, 5 joint activities were undertaken: a 1-day, in-library use survey; a wayfinding study, in which 10 new students were filmed as they searched for 3 items in the library; 5 focus group sessions regarding upcoming library renovations; a LibQUAL+® survey measuring perceptions of service quality among the entire campus population; and an online survey of non-users of the library. The success of the assessment/marketing projects was measured by the response rates, the representativeness of the results, and the number of free-text comments with rectifiable issues. Results – Although the response rates were not very high in any of the surveys, they were very representative of the university population. With over 40% or respondents filling in free-text comments, the information received was used and applied in making service changes, including the creation and marketing of additional group study rooms, improved signage, and the launch of a “quiet” campaign. In addition, a “You said – We did” document was compiled that outlines all of the changes that were implemented since the first four surveys were conducted; this document was published on the library’s blog, Facebook page, and website. Conclusion – The number of issues that appear in the first “You said – We did” document is a testament to the close and ongoing collaboration between the two teams, from the planning stages of each survey until publication of results and notification of the changes that were implemented.